Acute Streptococcal Tonsillopharyngitis in Children: Questions of Diagnosis and Therapy - Ye.I. Yulish; O.Ye. Chernysheva; B.I. Krivuschev; Ye.V. Glinskaya (Zdorovʹe Rebenka, 2013)
The article presents the current views on approaches to diagnosis and rational therapy of acute tonsillopharyngitis in children.